2022
DOI: 10.3201/eid2802.211834
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mRNA BNT162b2 Vaccine 6 Months after Vaccination among Patients in Large Health Maintenance Organization, Israel

Abstract: Israel experienced a new wave of coronavirus disease during June 2021, six months after implementing a national vaccination campaign. We conducted 3 discrete analyses using data from a large health maintenance organization in Israel to determine whether IgG levels of fully vaccinated persons decrease over time, describe the relationship between IgG titer and subsequent PCR-confirmed infection, and compare PCR-confirmed infection rates by period of vaccination. Mean IgG levels steadily decreased over the 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 16 publications
4
32
1
Order By: Relevance
“…Where population-based studies have been done, 4,7,8 these did not compare the effect of two doses of viral vector vs mRNA vaccines on host response; neither did they systematically ascertain participants' pre-vaccination SARS-CoV-2 serostatus, which is an important potential confounder of associations reported. Moreover, these studies did not investigate effects of modifiable factors that have been posited to influence responses to vaccination, such as time of day of inoculation, 14 nutrition, 15 sleep, 16 alcohol use, 17 tobacco smoking 18 and peri-vaccination use of anti-pyretic analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Where population-based studies have been done, 4,7,8 these did not compare the effect of two doses of viral vector vs mRNA vaccines on host response; neither did they systematically ascertain participants' pre-vaccination SARS-CoV-2 serostatus, which is an important potential confounder of associations reported. Moreover, these studies did not investigate effects of modifiable factors that have been posited to influence responses to vaccination, such as time of day of inoculation, 14 nutrition, 15 sleep, 16 alcohol use, 17 tobacco smoking 18 and peri-vaccination use of anti-pyretic analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…3 Existing studies investigating determinants of vaccine immunogenicity have reported that lower antibody responses following SARS-CoV-2 vaccination associate with administration of viral vector vs messenger RNA (mRNA) vaccines, older age, poorer general health, immunosuppression and shorter inter-dose intervals. [4][5][6][7][8][9][10][11] Higher postvaccination antibody titres are seen in those with evidence of SARS-CoV-2 infection before vaccination. 9,12,13 However, these studies are limited in several respects: many are conducted in specific populations such as health care workers 5,9,12,13 or in individuals with a particular demographic or clinical characteristic that may influence vaccine immunogenicity, 6,10,11 which may constrain generalisability of their results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results, at 14–90 days after standard two doses of mRNA‐1273, the efficacy against the Omicron and Delta variants were 30.4% and 62.5%, respectively 92 . The vaccine effectiveness data of the ChAdOx1, BNT162b2, and mRNA‐1273 vaccines against WT SARS‐CoV‐2, Delta, and Omicron variants is summarized in Table 1 91,93–100 …”
Section: Immune Evasion Of Sars‐cov‐2 Omicronmentioning
confidence: 99%
“… 92 The vaccine effectiveness data of the ChAdOx1, BNT162b2, and mRNA‐1273 vaccines against WT SARS‐CoV‐2, Delta, and Omicron variants is summarized in Table 1 . 91 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 …”
Section: Immune Evasion Of Sars‐cov‐2 Omicronmentioning
confidence: 99%